Levels of concentrates and protein sources in intensive pasture-based beef cattle rearing during the rainy season in the Amazon biome - Artur Carmanini de Faria; Dheyme Cristina Bolson; Douglas dos Santos Pina; Carla Silva Chaves; Thiago Trento Biserra; Thiago Alves Prado; Dalton Henrique Pereira (PLoS ONE, 2025)
This study aimed to evaluate the effects of different nutritional strategies on the intensification of beef cattle farming on pastures during the rainy season. Eighty male cattle (testers) were randomly allocated to 16 paddocks formed with Mombaça grass (Megathyrsus maximus), totaling five animals (testers) per paddock. The strategies consisted of two levels of concentrates (LC) [7 and 10 g.kg-1 of body weight (BW)], i.e., low and high LC, and two protein sources (PS) with dried distillers’ grain with solubles (DDGS) and soybean meal (SBM) in a completely randomized design with a 2 × 2 factorial arrangement. The forage’s chemical, structural, and productive characteristics and the supplemented animals’ performance, productivity, and serum parameters were evaluated. The forage had the greatest height (P = 0.038) at the lowest LC; however, a greater leaf proportion (P = 0.049) and leaf: stem ratio (L:S) (P = 0.042) were observed when the highest LC was used. The animals receiving the highest LC had the highest supplement intake (P < 0.001) and a lower pasture intake (P = 0.001). The average daily gain (ADG) did not differ between the LC (P = 0.135) and PS (P = 0.190) groups (0.97 kg.day-1). The LC used in the nutritional strategies did not affect the stocking rate (P = 0.272) or productivity (P = 0.986). Supplementation of 7 g.kg-1 BW is recommended for intensive rearing of beef cattle during the rainy season, as it results in high gains at a relatively low cost. In addition, as there were no negative responses to the use of DDGS as a protein source in the supplement, it represents an alternative for replacing soybean meal in the formulations.